O ser como começo da Ciência: a Ciência da Lógica de Hegel - Nicolau, Marcos Fábio Alexandre (2008)
The Hegelian refusal to entire Absolute suggests or post unrefletly demanded the establishment of a system of discursive and philosophical intelligible from the principle to the end. The idea is that the resulting possibility of intelligibility is the Absolute connection to the possibility of their exposure. That is, the inherent need it that needs to produce its own contents, extruding up while acknowledging its identity with itself, proving the need to start the effectiveness of a system of science that is based on a project of a science the logic founder of the science itself. Thus, the developing of a principle first–last speculation, the Hegelian philosophy, make clear the role of mediator, to liberate the system of methods and proposals outside and quotas that have condition. The result is that in the Science of Logic, the assumption of an early and immediate vacuum system of scientific-philosophical categories of the Absolute, and methodological speech in which it explains, must be described and explained, precisely due to the nature of the unconditional pure thought, which structure such bases to the said system. That is the task, apparently irrefutably the philosophy, to seek the union between being and thinking of a system that is capable of self-grounded and justified, donating solid basis not only to itself but to any science, which does be regarded as a genuine doctrine of science, able to establish the basic assumptions to any knowing that you want to say valid. As in Hegel made this feasible only on bases of a dialectical method, the fruit of the very nature of starting that brings you the inherent element of contradiction, denial determined, capable to promote self-development of a knowledge absolute said.